Modeling new processes for preparing sleeves before rolling - Bilodidenko , S.V.; Mazur, I.A.; Dobriak , V.D.; Uhriumov , Yu.D.; Uhriumov , D.Yu. (Theory and Practice of Metallurgy, 2024)
The purpose of this work is to develop new technological processes for preparing the ends of sleeves on a mandrel before rolling on a pilgrim tube rolling mill. Methodology. The work solves the problem of preparing the ends of the sleeves in the line for loading mandrels into them, which is carried out on the operating section of the pilgrim mill. Findings. To determine the energy-power parameters of the loading press force during the preparation of the rear end of the sleeve, the sliding line method was used, with the help of which changes in the force of distributing the rear end of the sleeve by the conical belt of the mandrel were calculated, taking into account the depth of its insertion. Originality. This allows you to determine the working length of the conical mandrel belt with its selected taper, taking into account the capabilities of the hydraulic cylinder of the filling press. Practical value. The proposed technology for preparing the ends of sleeves on the mandrel before pilgrim rolling allows reducing the unevenness of sleeves and pipes due to the concentric arrangement of the sleeve on the mandrel during the rolling process.